2002
DOI: 10.1073/pnas.102179999
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the C-terminal fragment of striated-muscle α-tropomyosin reveals a key troponin T recognition site

Abstract: Contraction in striated and cardiac muscles is regulated by the motions of a Ca 2؉ -sensitive tropomyosin͞troponin switch. In contrast, troponin is absent in other muscle types and in nonmuscle cells, and actomyosin regulation is myosin-linked. Here we report an unusual crystal structure at 2.7 Å of the C-terminal 31 residues of rat striated-muscle ␣-tropomyosin (preceded by a fragment of the GCN4 leucine zipper). The C-terminal 22 residues (263-284) of the structure do not form a two-stranded ␣-helical coiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 63 publications
9
112
1
Order By: Relevance
“…This arrangement differed from that in an NMR structure (24) of the junction, which is symmetric with splayed C termini. The crystal structures of C-terminal fragments in the absence of the N-terminal fragment showed a tail-tail interaction with splayed C termini (19,25). These results indicate that the C-terminal region can take up multiple configurations including a splayed one.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This arrangement differed from that in an NMR structure (24) of the junction, which is symmetric with splayed C termini. The crystal structures of C-terminal fragments in the absence of the N-terminal fragment showed a tail-tail interaction with splayed C termini (19,25). These results indicate that the C-terminal region can take up multiple configurations including a splayed one.…”
Section: Discussionmentioning
confidence: 62%
“…1A). The structure of P2 1 crystals containing both TM-N and TM-C was determined to 2.1 Å resolution by molecular replacement using the C-terminal region of tropomyosin (19) as template. The resultant composite omit map showed that residues 254-281 formed a coiled coil, even though the corresponding region in the template splayed after residue 270 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(In this model, in the Ca 2ϩ -activated azimuthal position, only a few electrostatic interactions between ␤ zone residues of tropomyosin and subdomain 4 of actin would appear to occur.) Note that a singular region of the tropomyosin filament is the overlap between consecutive molecules, which involves approximately nine residues from the N and C termini (52), as well as a non-coiled-coil stretch observed to extend from the C terminus back as far as residue 263 in structures of fragments (8,9). This region (residues 263-284) coincides precisely with the seventh ␤ zone; its location over a valley rather than in close contact with a ridge of actin would support the picture of an uninterrupted interaction between F-actin and a tropomyosin filament across the head-tail overlap (52).…”
Section: Azimuthal Positions and Polarity Of Tropomyosin On Actinmentioning
confidence: 99%
“…Structural studies have shown that TnT binds to Tm in an antiparallel manner, with its C-terminal domain positioned near residue 190 of Tm, and the N-terminal tail extending toward Tm's overlapping head-to-tail region (4,10). Studies of Stefancsik et al (63) have shown that residues 160-240 of human fast skeletal TnT (FTnT) contain a highly conserved domain characterized by a heptad repeat motif with the potential to form an α-helical coiled-coil (Fig.…”
Section: Troponin Tmentioning
confidence: 99%
“…Tm is a two-stranded α-helical coiled-coil composed of head-to-tail noncovalently bonded molecules winding around the actin helix (4). Tn is composed of three subunits which interact strongly with one another: the Ca 2+ -binding troponin C (TnC), the inhibitory troponin I (TnI) and the Tm-binding troponin T (TnT) subunits (Fig.…”
Section: Introductionmentioning
confidence: 99%